Recent Advances in the Synthesis of Electron Donor Conjugated Terpolymers for Solar Cell Applications - Gedefaw, Desta; Pan, Xun; Andersson, Mats R. (Frontiers in Materials, 2020)
The synthesis of donor (D)-acceptor (A) copolymers using structurally elaborated monomers is an active research field. Some of the challenges with the use of alternating D-A copolymers for photovoltaic applications are the relatively narrow absorption widths, the presence an absorption valleys in the visible region, unoptimized molecular energy levels and even lack of compatibility of the polymers with the common acceptors. The synthesis and characterization of polymers consisting of multiple chromophores (random and regular terpolymers) with complementing properties is currently gaining momentum in order to delicately optimize properties of polymers. A random terpolymer can either be of a system composed of one donor and two acceptors ((D-A1)-alt-(D-A2)) or a one acceptor and two donor segments ((D1-A)-alt-(D2-A)) incorporated in the polymer backbone. By varying the composition of the monomers in the feed of the polymerization reaction, the properties of the resulting terpolymers can be carefully optimized. Using this strategy, many materials with desired properties have been developed and power conversion efficiency (PCE) surpassing 14% in a single layer bulk heterojunction (BHJ) solar cell device have been reported. This review summarizes the most recent advances made in the development of terpolymers for organic photovoltaics (OPVs). The properties of the terpolymers are compared with those of reference binary polymers.